Evaluating Spatial Thinking Ability Using Item Response Theory: Differential Item Functioning Across Math Learning Disabilities and Geometry Instructions. (May 2021) - Choo, Sam; Park, Sunhi; Nelson, Nancy J.
Science, Technology, Engineering, and Mathematics (STEM) education initiatives have placed pressure on teachers to bring technology tools into classroom, including three-dimensional (3D) printing. Yet, little research has examined what specific math skills are required for 3D printing technology. This article describes a follow-up analysis of findings from a quasi-experimental study that tested feasibility of 3D geometry instruction, Anchored Instruction with Technology Applications (AITA), designed to help students visualize and construct 3D models based on Enhanced Anchored Instruction. Although we found that AITA improved math outcomes of students with math learning disabilities (MLD) in the previous analysis, we only used composite scores encompassing a variety of math and spatial tasks. In this study, we employed item response theory and differential item functioning to examine the impacts of MLD on students' spatial thinking skills, understand the types of items to assess the intended skills in a valid way, and provide a detailed information of whether student ability and MLD status have caused different results to assess students' spatial thinking skills. Results showed that students with MLD struggle to learn spatial thinking skills, and AITA was a significant positive indicator to improve spatial thinking skills for both students with and without MLD.